Analisis Jumlah Kuantitatif Kebutuhan Bahan Pustaka Monograp Perpustakaan IAIN Curup Berdasarkan Jumlah Mahasiswa Tahun 2019 - Maulana Syaid; Marleni Marleni; Rahmat Iswanto (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This paper is a quantitative analysis of research on the number of library material requirements for the 2019 Curup IAIN library based on students. The purpose of this study is to obtain a quantitative amount of library material requirements for the 2019 IAIN Curup library based on students so that the numerical calculations can be evaluated and planned for meeting the needs of the visitors. The data used is data on the number of students in 2019 which is spread into several study programs and divided again based on the year of the year and the current semester. Other data used is data on the number of subjects that are billed at IAIN Curup 2019. The method used is quantitative analysis using mathematical logic. The results obtained are the number of library monograph materials with units of titles and copies seen from the number of students per semester, per year, and the accumulated number for all students of IAIN Curup in 2019. From the quantitative analysis results can be estimated in general user needs. The amount is recalculated against special circumstances regarding changes in the number of students for several reasons. This research is useful for making the design and evaluation of the policy development of the IAIN Curup library collection.